EVALUASI PELAKSANAAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN DI KECAMATAN RUMBAI KOTA PEKANBARU (Studi Pemberian Rekomendasi Izin Pemondokan atau Rumah Kos) - Prihatin, Panca Setyo; Rusadi, Sylvina; Adni, Dita Fisdian (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2019)
One of the authority of the district head in the Act of the Rumbai District Head of Pekanbaru City Number: Kpts/23/KR/IX/2014 Regarding the Implementation of Integrated Administrative Services of the Districts in Rumbai District is in terms of granting recommendations for boarding permits or boarding houses. This is considered important because the boarding house business is considered profitable especially if it is located in strategic areas around the university as an educational center. However, this is not accompanied by the obligation of the business owner to take care of boarding house permits as a provision stipulated by the Pekanbaru City Government. Rumbai District is a strategic area for the establishment of several universities today, such as Lancang Kuning University (UNILAK), Caltex Riau Polytechnic (PCR), the Faculty of Health, University of Riau (UR) and others. From the results of interviews and observations of the Integrated District Administration Service (PATEN) in Rumbai District, Pekanbaru City (Study on Giving Recommendations for Boarding Permit or Boarding House) has not run according to the established Standard Operating Procedure (SOP). This can be seen from the existence of a number of complaints from the people who are taking care of a recommendation for a boarding house or boarding house recommendation about the service of the Rumbai sub-district office which is still lacking in terms of information on the Standard Operating Procedure (SOP) of the service and also regarding the time of completion of the recommendation letter.